2022
DOI: 10.1101/2022.02.11.480088
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Navigation of Ultrasound-controlled Swarmbots under Physiological Flow Conditions

Abstract: Navigation of microrobots in living vasculatures is essential in realizing targeted drug delivery and advancing non-invasive surgeries. We developed acoustically-controlled swarmbots based on the self-assembly of clinically-approved microbubbles. Ultrasound is noninvasive, penetrates deeply into the human body, and is well-developed in clinical settings. Our propulsion strategy relies in two forces: the primary radiation force and secondary Bjerknes force. Upon ultrasound activation, the microbubbles self-asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…We studied microrobot formation and navigation in 3D microfluidic channels with circular cross-sections. We demonstrated that the motion-control mechanism we presented in previous studies could also move microrobots in 3D setups having arbitrary angles and relative positions of the transducer and target vessel (50). The microrobots in this study are formed by the aggregation of single gas-filled microbubbles under the influence of an acoustic wave (50).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…We studied microrobot formation and navigation in 3D microfluidic channels with circular cross-sections. We demonstrated that the motion-control mechanism we presented in previous studies could also move microrobots in 3D setups having arbitrary angles and relative positions of the transducer and target vessel (50). The microrobots in this study are formed by the aggregation of single gas-filled microbubbles under the influence of an acoustic wave (50).…”
Section: Resultsmentioning
confidence: 83%
“…We demonstrated that the motion-control mechanism we presented in previous studies could also move microrobots in 3D setups having arbitrary angles and relative positions of the transducer and target vessel (50). The microrobots in this study are formed by the aggregation of single gas-filled microbubbles under the influence of an acoustic wave (50). Secondary Bjerknes forces initiate the microbubble swarms, which are then translated along the vessels by primary radiation forces.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…ULM allows localization and tracking of microbubbles within 10 microns in resolution, and accurate 3D measurements of their velocities (∼ mm/s) deep in organs 37 . Additionally, the type of powering we studied in this article preserves the displacement's degrees of freedom: (i) the swimmer is activated by a scalar parameter, namely pressure, which precludes any reorientation effect that may affect, e.g., swimmers activated by magnetic fields (ii) the swimming direction is completely independent of the direction of the activation wave, by contrast with microbubble control mechanisms based on the primary radiation force ("Bjerkness forces") 38 . In a complex 3D environment such as the human microvasculature where important exchanges with the vessel walls take place, having a swimmer whose propelling direction is independent of the actuator features is a key point.…”
Section: /11mentioning
confidence: 99%
“…Thus, a dual-frequency ultrasound probe can achieve simultaneously propulsion and real time imaging 38,39 . Additionally, the type of powering we studied in this article preserves the displacement's degrees of freedom: (i) the swimmer is activated by a scalar parameter, namely pressure, which precludes any reorientation effect that may affect, e.g., swimmers activated by magnetic fields (ii) the swimming direction is completely independent of the direction of the activation wave, by contrast with microbubble control mechanisms based on the primary radiation force ("Bjerkness forces") 40 . In a complex 3D environment such as the human microvasculature where important exchanges with the vessel walls take place, a swimmer whose propelling direction is independent of the actuator features is a key point.…”
Section: Towards Tunable High Velocitiesmentioning
confidence: 99%